Navigating Digital Credit: How Risky Indebtedness Behavior and Impulsive Buying Shape Buy-Now-Pay-Later Intention? - Hesniati, Hesniati; Phangestu, Steffany Jessica; Marheni, Dewi Khornida; Arviano, Hengky (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2025)
Objective: This study examines the psychological factors influencing consumers’ intention to use Buy Now Pay Later (BNPL) services, focusing on the roles of risky indebtedness behavior, impulsive buying, and attitude toward credit, while exploring gender-based differences. Design/Methods/Approach: Drawing on the Theory of Planned Behavior and Self-Regulation Theory, data were collected from 401 BNPL users using an online survey. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and multigroup analysis by gender. Findings: Risky indebtedness behavior, impulsive buying, and attitude toward credit significantly influence BNPL intention, with attitude serving as a key mediator. Impulsive buying indirectly affects BNPL intention through risky indebtedness and attitude toward credit. The multigroup analysis reveals that male consumers’ BNPL intention is more strongly influenced by impulsive buying, whereas female consumers’ intention is driven primarily by risky indebtedness behavior through attitude toward credit. Originality/Value: This study contributes to behavioral finance research by integrating TPB and SRT to explain BNPL adoption behavior. It offers new insights into how gender differences shape the psychological mechanisms in credit-based consumption. Practical/Policy implication: BNPL providers should tailor strategies such as targeted spending alerts and marketing campaigns to address behavioral differences across gender groups. Regulators should focus on enhancing digital financial literacy and self-regulation awareness, ensuring transparent product information, enforcing spending limits, and integrating educational programs to mitigate risky indebtedness and impulsive buying behaviors.